2003
DOI: 10.1590/s0036-46652003000100005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surrogate markers for human immunodeficiency virus infection among blood donors at the blood bank of "Hospital Universitário Regional Norte do Paraná", Londrina, PR, Brazil

Abstract: This study evaluated the usefulness of the anti-HBc, hepatitis C virus antibodies (anti-HCV), human T cell lymphotropic virus I and II antibodies (anti-HTLV I/II), serologic tests for syphilis, and surface antigen of hepatitis B virus (HBsAg) as surrogate markers for the risk for HIV infection in 80,284 serum samples from blood donors from the Blood Bank of "Hospital Universitário Regional Norte do Paraná", Londrina, Paraná State, Brazil, analyzed from July 1994 to April 2001. Among 39 blood donors with positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
2
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
2
4
2
2
Order By: Relevance
“…The importance of this marker is thus confirmed; it serves as a marker for the risk of other viral infections. Its association with HIV infection in this study is in agreement with the findings of Reiche et al (24) ; this possibly occurs owing to the fact that these viral infections share a common means of transmission.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The importance of this marker is thus confirmed; it serves as a marker for the risk of other viral infections. Its association with HIV infection in this study is in agreement with the findings of Reiche et al (24) ; this possibly occurs owing to the fact that these viral infections share a common means of transmission.…”
Section: Discussionsupporting
confidence: 93%
“…This is in disagreement with the findings of Reiche et al (24) and Herrera et al (25) , whose conclusions were that the syphilis test is of little importance as an indirect marker for identifying and excluding donations by individuals presenting a high risk of HIV infection. There seems, however, to be some controversy on this subject in the literature: in Ethiopia, Rahlenbeck et al (26) found that HIV positive donors presented a higher risk of being syphilis positive.…”
Section: Discussioncontrasting
confidence: 71%
“…The use of surrogate markers for HIV infection among blood donors has been suggested. 9 The authors showed anti-HBc and anti-HCV as useful surrogate markers for HIV infection in blood donors. In addition, they speculated that screening for these surrogate markers may prevent the small number of cases in which HIV is still transmitted by transfusion.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of rejecting donated blood is enormous, given that there is such a great shortage of volunteer donors. On the other hand, accurate tests are increasingly necessary to prevent the risk of contracting an infection by receiving a blood unit unduly released [13][14][15].…”
Section: Introductionmentioning
confidence: 99%